2015
DOI: 10.1016/j.jallcom.2015.05.235
|View full text |Cite
|
Sign up to set email alerts
|

MAX phase Ti2AlC foams using a leachable space-holder material

Abstract: MAX phase foams from commercial Ti 2 AlC powder were prepared by a novel powder processing method using raw sugar as space-holder. Manufacturing MAX phase foams using this method involves mixing Ti 2 AlC powder with raw sugar, pressing the mixture to form a green body followed by space-holder removal and sintering. Green bodies were formed using cold uniaxial pressing and porosity was controlled varying the size and amount of the raw sugar space-holder. Three different space-holder particles sizes in the range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…So far, the majority of studies reported on these materials focus on dense components. Research on porous Ti 2 AlC and other MAX phases is rather limited . Porous MAX phases need systematic studies, because control of the porosity and pore size can be used to tailor their functional properties.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…So far, the majority of studies reported on these materials focus on dense components. Research on porous Ti 2 AlC and other MAX phases is rather limited . Porous MAX phases need systematic studies, because control of the porosity and pore size can be used to tailor their functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…Porous MAX phases need systematic studies, because control of the porosity and pore size can be used to tailor their functional properties. For example, porous Ti 2 AlC is an attractive material for high‐performance applications such as electrode materials for harsh chemical environment, microbial fuel cells (MFCs), and solar volumetric collectors . Porous Ti 2 AlC with a high level of open porosity can also be used as preform for metal‐ceramic interpenetrating composites in order to produce materials with exceptional damping properties .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations